1997
DOI: 10.1038/ng0497-363
|View full text |Cite
|
Sign up to set email alerts
|

A high observed substitution rate in the human mitochondrial DNA control region

Abstract: The rate and pattern of sequence substitutions in the mitochondrial DNA (mtDNA) control region (CR) is of central importance to studies of human evolution and to forensic identity testing. Here, we report a direct measurement of the intergenerational substitution rate in the human CR. We compared DNA sequences of two CR hypervariable segments from close maternal relatives, from 134 independent mtDNA lineages spanning 327 generational events. Ten substitutions were observed, resulting in an empirical rate of 1/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
283
4
10

Year Published

1998
1998
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 419 publications
(309 citation statements)
references
References 35 publications
12
283
4
10
Order By: Relevance
“…Typical values for accumulation of mtDNA point mutations in humans have been thought to be in the order of 10 Ð6 Ð10 Ð8 (estimated from Brown et al 1979; Kondo et al 1993). A recent study sequencing the hypervariable domains of the human control region from large pedigrees, however, indicates a per generation rate larger than previously reported and much more similar to those observed for mtVNTRs (Parsons et al 1997).…”
Section: Mutation Rates In Mtvntrsmentioning
confidence: 85%
“…Typical values for accumulation of mtDNA point mutations in humans have been thought to be in the order of 10 Ð6 Ð10 Ð8 (estimated from Brown et al 1979; Kondo et al 1993). A recent study sequencing the hypervariable domains of the human control region from large pedigrees, however, indicates a per generation rate larger than previously reported and much more similar to those observed for mtVNTRs (Parsons et al 1997).…”
Section: Mutation Rates In Mtvntrsmentioning
confidence: 85%
“…A recent study revealed a higher frequency of mtDNA variations in women with RPL [9]. Most of these mutations accumulate in the regulatory region or D-loop [10]. Since D-loop has a regulatory role on mtDNA replication and transcription, mutations in this region might have an important effect in copy number and gene expression of the mitochondrial genome, and could disturb mitochondrial function, oxidative phosphorylation (OXPHOS) and ATP production.…”
Section: Introductionmentioning
confidence: 99%
“…This approach can also not detect insertion-deletion variation, which must be addressed by other means (Keightley & Eyre-Walker, 2000). Direct sequencing gives estimates of mutation rate an order of magnitude higher than do interspecific comparisons, suggesting that the bias is large (Howell et al, 1996 ;Parsons et al, 1997;Denver et al, 2000). However, it is not clear that direct sequencing is necessarily more accurate, because the impact of sequencing errors has yet to be adequately addressed.…”
Section: Introductionmentioning
confidence: 99%